The Implementation of SEOJK No. 16/2021 Regulation and External Assurance Statements on Corporate Sustainability Reporting on Indonesia Stock Exchange - Tiara Chairunissa F; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the implementation of SEOJK No. 16/2021 regulation, external assurance statements on corporate sustainability reporting with firm size as control variable. The population on this research is several manufacturing company listed on Indonesian Stock Exchange on 2020 and 2022. This study used secondary data. The sampling technique used simple random sampling method with 290 firm as the sample for 2 years. Using multiple regression as data analysis technique on this research. The result showed that SEOJK no.16/ 2021 regulation had an effect on corporate sustainability reporting. Meanwhile, external assurance statements and firm size has no effect on corporate sustainability reporting.